MARSHALL CHARACTERISTIC OF SPLIT MASTIC ASPHALT WITH CELLULOSE KAPUK FIBER ADDITION - Riza Millatul Aminin; Akhmad Hasanuddin; Dewi Junita Koesoemawati (Universitas Jember, 2020)
Split Mastic Asphalt (SMA) mixture is mostly used on heavy traffic roads. SMA mixture has high percentage of coarse aggregate, it is better able to withstand deformation due to heavy vehicles, and consist of high levels of asphalt, that makes the mixture more durable. High levels of asphalt in SMA require an additive as fiber, polymer, filler, and PET which functions to stabilize and increase the strength of the mixture. This study to determine the performance of the Split Mastic Asphalt mixture by adding kapuk fiber as an additive. The method used is a quantitative comparison of the marshall SMA test results without the addition of additives and the SMA mixture with the addition of cotton fiber as an additive. The variation of cotton fiber content used in the mixture is 0.01%, 0.025%, 0.05%, 0.075% and 0.1% of weight mixture. Based on the results of the study the addition of cotton fiber to the mixture can improve Marshall performance in terms of strength, density, and durability of the mixture. The strength of the mixture with the addition of cotton fiber will increase to the optimum limit, which is 0.075% cotton fiber. The density of the mixture (density) with the addition of cotton fiber will increase. Durability based on flow and MQ values decreased, but increased again at high cotton fiber levels, which is 0.1% Campuran Split Mastic Asphalt merupakan campuran yang banyak digunakan pada jalan berlalulintas berat. Campuran SMA memiliki persentase agregat kasar tinggi sehingga lebih mampu menahan deformasi akibat kendaraan berat dan kadar aspal tinggi, sehingga campuran akan lebih tahan lama. Tingginya kadar aspal pada campuran SMA membutuhkan suatu aditif berupa serat, polimer, filler, dan PET yang berfungsi untuk menstabilkan dan meningkatkan kekuatan campuran. Penelitian ini bertujuan untuk mengetahui kinerja campuran Split Mastic Asphalt dengan penambahan serat kapuk sebagai aditif. Metode yang digunakan adalah perbandingan kuantitatif hasil pengujian marshall campuran SMA tanpa penambahan aditif dan campuran SMA dengan penambahan serat kapuk sebagai aditif. Variasi kadar serat kapuk yang digunakan pada campuran adalah 0,01%, 0,025%, 0,05%, 0,075% dan 0,1% terhadap berat campuran. Berdasarkan hasil penelitian penambahan serat kapuk terhadap campuran dapat meningkatkan kinerja marshall yang ditinjau dari kekuatan, kepadatan, dan keawetan campuran. Kekuatan campuran dengan penambahan serat kapuk akan semakin meningkat hingga pada batas optimum, yaitu 0,075% serat kapuk. Kepadatan campuran (density) dengan penambahan serat kapuk akan semakin meningkat hingga pada bata optimum penambahan 0,05 serat kapuk. Keawetan berdasarkan nilai flow dan MQ menurun, namun meningkat kembali pada kadar serat kapuk tinggi, yaitu 0,1%.